Mengelola Waktu dengan Efektif: Strategi untuk Meningkatkan Produktivitas Hidup Bagi Anak Madrasah Diniyah Takmiliyah - Sembiring, Putri Pebrija; Sianturi, Mian; Khairani, Dewi; Sinaga, Jelita Tessalonika; Naibaho, Yuni Naftalia; Sari, Imelda; Manullang, Thomas Ridoansih; Yusnadi, Yusnadi; Subaedah, Sitti (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to understand the time management strategies employed by students at Madrasah Diniyah Takmiliyah and to identify the factors that influence their ability to manage time. This research uses a qualitative descriptive approach with a case study type. The data collection techniques used are observation, interviews, and documentation. The collected data was analyzed using a thematic analysis method, which consisted of three main stages: data reduction, data presentation, and conclusion drawn. The results of the study indicate that students at Madrasah Diniyah Takmiliyah still face difficulties in managing their time efficiently. Factors such as procrastination, inaccurate time estimation, and lack of priority are the main obstacles in student time management. This study also found that well-defined goals, internal motivation, and commitment to self-improvement are significant supporting factors in student time management. By applying effective time management strategies and understanding the factors that influence them, students at Madrasah Diniyah Takmiliyah can improve their learning productivity and achieve their expected academic goals.